2012
DOI: 10.2478/s11756-012-0111-0
|View full text |Cite
|
Sign up to set email alerts
|

Estimating effects of global warming from past range changes for cold demanding refugial taxa: A case study on South-west Anatolian species Poecilimon birandi

Abstract: Although changes in biodiversity and in ecosystems are surely caused by a range of interacting drivers, such as natural or human-induced factors, one of the important drivers having major impacts on climate and biodiversity and leading to range changes and fragmentation is global warming. Defining past range changes/fragmentations during interglacial periods may provide tools to understand possible impacts of global warming on present biodiversity. To test this assumption we studied a marker gene in the bush-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 64 publications
1
27
0
1
Order By: Relevance
“…The founder populations moved from these southern refugial areas during the hot interglacial periods to reestablish the biodiversity of northern areas. Many scientists think that Anatolia was an important Pleistocene glacial refugium (Çıplak, 2004;Kaya et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The founder populations moved from these southern refugial areas during the hot interglacial periods to reestablish the biodiversity of northern areas. Many scientists think that Anatolia was an important Pleistocene glacial refugium (Çıplak, 2004;Kaya et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…; Kaya et al. ). Neutrality tests and mismatch distributions clearly indicated that Clade III had gone through a recent rapid expansion.…”
Section: Discussionmentioning
confidence: 97%
“…; Kaya et al. ) advocating the widespread involvement of the mid‐Pleistocene revolution for divergence within Anatolian mountains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations